Computational insights into the adsorption mechanism of gallic acid-bearing reagents on calcium-bearing mineral surfaces. (1st September 2020) - He, Jianyong; Hu, Yuehua; Sun, Wei; Zhang, Chenyang; Zhang, Chenhu; Lin, Shangyong; Zou, Jingxiang
Graphical abstract: Highlights: TA prefers to adsorb onto the calcite surface rather than the fluorite surface, but pyGA/GA are the opposite. The balance of the chemical force and VdW force is responsible for the interaction difference. Precisely predicating the performance of flotation reagents needs to consider spatial structures of big molecules and mineral surface structures. Abstract: Interaction mechanisms of flotation reagents including pyrogallic acid (pyGA), GA and tannic acid (TA) adsorption onto fluorite (1 0 0) and calcite (1 0 4) surfaces were investigated by first-principles calculations, molecular mechanics (MM) and molecular dynamics (MD) approaches under vacuum phases to understand the spatial effects of molecules. First-principles calculations indicated that GA/pyGA could more strongly adsorb onto the fluorite surface than onto the calcite surface, but MM and MD results indicated TA tended to adsorb onto the calcite surface rather than the fluorite surface. These results were consistent with reported flotation results. Further analysis showed that the interaction difference was ascribed to the different balance of the corresponding chemical and van der Waals forces on different mineral surfaces.